Updated Postlicensure Surveillance of the Meningococcal C Conjugate Vaccine in England and Wales: Effectiveness, Validation of Serological Correlates of Protection, and Modeling Predictions of the Duration of Herd Immunity - Campbell, Helen (American Society for Microbiology (ASM), 2010)
Meningococcal serogroup C conjugate (MCC) vaccines were licensed in the United Kingdom more than 10 years ago based on correlates of protection that had previously been established for serogroup C-containing polysaccharide vaccines by using the serum bactericidal antibody (SBA) assay. These correlates of protection were subsequently validated against postlicensure estimates of observed vaccine effectiveness up to 7 to 9 months after the administration of the MCC vaccine. Vaccine effectiveness was, however, shown to fall significantly more than 1 year after the administration of a 3-dose course in infancy. Despite this finding, the marked impact on serogroup C disease has been sustained, with the lowest recorded incidence (0.02 case per 100,000 population) in the 2008-2009 epidemiological year, mainly due to the indirect herd immunity effect of the vaccine in reducing carriage. Updated estimates of vaccine effectiveness through 30 June 2009 confirmed high short-term protection after vaccination in infancy, at 97% (95% confidence interval [CI], 91% to 99%), falling to 68% (95% CI, −63% to 90%) more than a year after vaccination. The observed vaccine effectiveness more than 12 months postvaccination was consistent with measured declining SBA levels, but confidence intervals were imprecise; vaccine effectiveness estimates were consistent with SBA titers of 1:4 or 1:8 as correlates of long-term protection after a primary course in infants. Modeling suggested that protection against carriage persists for at least 3 years and predicted the stabilization of serogroup C disease at low levels (fewer than 50 cases per year) up to 2015-2016.